2023
DOI: 10.3389/fendo.2023.1230206
|View full text |Cite
|
Sign up to set email alerts
|

The effects of subcutaneous Tirzepatide on obesity and overweight: a systematic review and meta‐regression analysis of randomized controlled trials

Pejman Rohani,
Nasser Malekpour Alamdari,
Seyedeh Elaheh Bagheri
et al.

Abstract: BackgroundDespite the fact that obesity and overweight are serious major health problems worldwide, fighting against them is also considered a challenging issue. Several interventional studies have evaluated the potential weight-reduction effect of Tirzepatide. In order to obtain a better viewpoint from them, this study aimed to comprehensively investigate the effects of subcutaneous Tirzepatide on obesity and overweight.MethodsScopus, PubMed/Medline, Web of Science, Cochrane, and Embase databases were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…24 A systematic review and meta-analysis included 7062 participants and pooled findings showed significant body weight, BMI, and waist circumference reduction with tirzepatide compared to placebo. 96…”
Section: Dual In Cre Tin Ag Onis Tsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 A systematic review and meta-analysis included 7062 participants and pooled findings showed significant body weight, BMI, and waist circumference reduction with tirzepatide compared to placebo. 96…”
Section: Dual In Cre Tin Ag Onis Tsmentioning
confidence: 99%
“…However, SURMOUNT trials have focused on studying tirzepatide and obesity and showed significant and sustained weight loss up to 20.9% mean change in body weight at 15 mg, compared to placebo 24 . A systematic review and meta‐analysis included 7062 participants and pooled findings showed significant body weight, BMI, and waist circumference reduction with tirzepatide compared to placebo 96 …”
Section: Dual Incretin Agonistsmentioning
confidence: 99%
“…Another, meta-regression analysis was done by Rohani et al, on the effect of Tirzepatide on body weight. In congruence with other studies, here also, the overall findings showed a significant reduction in body weight (-11.34 kg [-12.79 to -9.88] P<0.001), body mass index (-3.11 [-4.36 to -1.86] kg/m 2 , P<0.001), and waist circumference (-7.24 [-10.12 to -4.36] cm, P< 0.001) [ 28 ]. A meta-analysis was published on the safety of Tirzepatide by Zeng Q et al, in October 2023, whereby, Tirzepatide was not found to be significantly associated with an increased risk of pancreatitis when compared to all control groups consisting of basal insulin (glargine or degludec), selective GLP1-RA (dulaglutide or semaglutide once weekly), and placebo (RR 1.46, [95% CI] 0.59 to 3.61; I2 = 0.0%, p = 0.436).…”
Section: Reviewmentioning
confidence: 99%
“…Three systematic reviews and meta-analyses have been published in 2023, documenting the weight loss benefits of tirzepatide (Lin et al, 2023;Rohani et al, 2023;Tan et al, 2023), with one drawing attention to the need for vigilance regarding gastrointestinal adverse effects (Lin et al, 2023).…”
Section: Dual Incretin Agonistsmentioning
confidence: 99%